Evolutionary analysis of the Delta and Delta Plus variants of the SARS-CoV-2 viruses - Kannan, Saathvik R.; Spratt, Austin N.; Cohen, Alisha R.; Naqvi, S. Hasan; Chand, Hitendra S.; Quinn, Thomas P.; Lorson, Christian L.; Byrareddy, Siddappa N.; Singh, Kamal (JOURNAL OF AUTOIMMUNITY, 2021)
Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) has been rapidly evolving in the form of new variants. At least eleven known variants have been reported. The objective of this study was to delineate the differences in the mutational profile of Delta and Delta Plus variants. High-quality sequences (n = 1756) of Delta (B.1.617.2) and Delta Plus (AY.1 or B.1.617.2.1) variants were used to determine the prevalence of mutations (≥20 %) in the entire SARS-CoV-2 genome, their co-existence, and change in prevalence over a period of time. Structural analysis was conducted to get insights into the impact of mutations on antibody binding. A Sankey diagram was generated using phylogenetic analysis coupled with sequence-acquisition dates to infer the migration of the Delta Plus variant and its presence in the United States. The Delta Plus variant had a significant number of high-prevalence mutations (≥20 %) than in the Delta variant. Signature mutations in Spike (G142D, A222V, and T95I) existed at a more significant percentage in the Delta Plus variant than the Delta variant. Three mutations in Spike (K417N, V70F, and W258L) were exclusively present in the Delta Plus variant. A new mutation was identified in ORF1a (A1146T), which was only present in the Delta Plus variant with ~58 % prevalence. Furthermore, five key mutations (T95I, A222V, G142D, R158G, and K417N) were significantly more prevalent in the Delta Plus than in the Delta variant. Structural analyses revealed that mutations alter the sidechain conformation to weaken the interactions with antibodies. Delta Plus, which first emerged in India, reached the United States through England and Japan, followed by its spread to more than 20 the United States. Based on the results presented here, it is clear that the Delta and Delta Plus variants have unique mutation profiles, and the Delta Plus variant is not just a simple addition of K417N to the Delta variant. Highly correlated mutations may have emerged to keep the structural integrity of the virus. •Delta Plus, which emerged from the Delta, has a distinct mutation profile.•A more significant number of high-prevalence mutations in Delta Plus than in Delta.•Delta Plus has new mutations in ORF1a (A1146T, P1604L, A3209V, V3718S, and T3750I).•Mutations alter the local structure to evade antibody binding.